Mechanical small bowel obstruction following a blunt abdominal trauma: A case report - Zirak-Schmidt, Samira (Ann Med Surg (Lond), 2015)
INTRODUCTION: Intestinal obstruction following abdominal trauma has previously been described. However, in most reported cases pathological finding was intestinal stenosis. PRESENTATION OF THE CASE: A 51-year-old male was admitted after a motor vehicle accident. Initial focused abdominal sonogram for trauma and enhanced computerized tomography were normal, however there was a fracture of the tibia. Three days later, he complained of abdominal pain, constipation, and vomiting. An exploratory laparotomy showed bleeding from the omentum and mechanical small bowel obstruction due to a fibrous band. DISCUSSION: The patient had prior abdominal surgery, but clinical and radiological findings indicate that the impact of the motor vehicle accident initiated his condition either by causing rotation of a bowel segment around the fibrous band, or by formation of a fibrous band secondary to minimal bleeding from the omentum. CONCLUSION: High index of suspicion of intestinal obstruction is mandatory in trauma patients presenting with complaints of abdominal pain, vomiting, and constipation despite uneventful CT scan.